"Not Pure Harmony, but Less of a Power Struggle": What Do Teachers and Pedagogues Think About Using Existential Pedagogy?. Issue 1 (2nd January 2018) - Siller, Heidi; Waibel, Eva Maria
Abstract: Existential Pedagogy (EP) derives from existential analysis and logotherapy developed by Viktor Frankl and Alfried Längle in the tradition of existential philosophy and phenomenology. This study investigated how EP influences pedagogues' and teachers' attitudes and teaching. Four focus groups with a total of 12 persons each were conducted in an elementary school that is tailored for students with emotional and behavioral problems. Data were analyzed with the qualitative content analysis. EP helped teachers come into relationship with students, strengthen students' self-esteem, and find meaningful approaches to the learning content. It also facilitated coming into touch with one's emotions and with the children's emotions. The individualized approach does not solely focus on children but highly impacts teachers and pedagogues. Similarities to other pedagogies can be found, but it appears to be specific for EP to have an impact on teachers and pedagogues. Additionally EP encourages an individual and flexible handling of EP.